The Relationship Between Parenting Styles and Nutritional Status of Toddlers in RW 11 Posyandu Nusa Indah, Kelurahan Tosaren - Reny Mareta Sari; Sergiana; Kurniawati, Janik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2025)
Effective parenting styles can significantly enhance the nutritional status of children. Poor nutritional status in toddlers can negatively impact their growth and development. This study aims to analyze the relationship between parenting styles and the nutritional status of toddlers in RW 11 Posyandu Nusa Indah, Kelurahan Tosaren. This study utilized a descriptive correlational design with a cross-sectional approach. It was conducted in RW 11 Posyandu Nusa Indah, Kelurahan Tosaren, in September 2023, with a sample size of 56 respondents. The research instrument was a questionnaire. Data analysis was performed using the chi-square test with α ≤ 0.05. The demographic results showed that the majority of respondents, 41 individuals (73.2%), were aged 20-35 years, 36 individuals (64.3%) had a high school education, and 29 individuals (51.8%) were housewives. Most toddlers, 31 individuals (55.4%), were male, and 14 individuals (25.0%) were aged 49-60 months. Parenting styles were categorized as poor (9 individuals, 16.1%), adequate (18 individuals, 32.1%), and good (29 individuals, 51.8%). The nutritional status of toddlers was classified as poor (1 individual, 1.8%), undernourished (4 individuals, 7.1%), normal (40 individuals, 71.4%), and overweight (11 individuals, 19.6%). Data analysis indicated a significant relationship between parenting styles and the nutritional status of toddlers in RW 11 Posyandu Nusa Indah, Kelurahan Tosaren (p-value 0.027 < 0.05). There is a significant relationship between parenting styles and the nutritional status of toddlers in RW 11 Posyandu Nusa Indah, Kelurahan Tosaren.